GenomeConnect: Matchmaking Between Patients, Clinical Laboratories, and Researchers to Improve Genomic Knowledge. Issue 10 (6th August 2015) - Kirkpatrick, Brianne E.; Riggs, Erin Rooney; Azzariti, Danielle R.; Miller, Vanessa Rangel; Ledbetter, David H.; Miller, David T.; Rehm, Heidi; Martin, Christa Lese; Faucett, W. Andrew; On Behalf of the ClinGen Resource
<x xml:space="preserve">Abstract</x> GenomeConnect is a project supported by the Clinical Genome Resource (ClinGen) providing the opportunity for patients to add to the genomics knowledge base by securely sharing health history and genetic test results. This paper covers a variety of topics including project development, the special roles of patients and laboratories, the relationship between GenomeConnect and the ClinVar database, the matchmaking capabilities of GenomeConnect, and the partnerships that GenomeConnect helps to form to increase data sharing and advance precision medicine.